Effect of cooking and drying on carbonyls of oil sardine - Devadasan, K., Ammu, K. and (Fishery Technology, 2021)
Changes in the total as well as major individual carbonyls of oil sardine during steam cooking, oven drying, sun drying and freeze drying are presented. Carbonyls extracted with hexane were converted to their 2:4 dinitro phenyl hydrazone (DNPH) derivatives and were separated into major classes by column chromatography on celite/magnesia. Individual carbonyls were then identified by capillary gas chromatography of the DNPH derivatives. Dehydration and heating increase the carbonyl production from highly unsaturated fish lipids. The carbonyls produced react with other muscle constituents leading to complex changes. The influence of the mode of dehydration on these different aspects and their net effect on flavour are discussed.